(untitled) (Advancements in Homeopathic Research, 2025)
The English language has many positive aspects, such as its wide acceptance, its reputation as an academic language, and the ability to offer a broad array of literature in digital and print formats. Overall, like many other disciplines, there are various advantages to the widespread use of English in global collaboration and research dissemination in homeopathy as it enhances the reach and credibility of the discipline and equality. The English language’s wide adoption contributes to offering a global forum for the exchange of innovative concepts and scientific discoveries, which can promote a more diverse and robust international research environment in Homoeopathy. Conversely, it is imperative to acknowledge and tackle the constraints, difficulties, and possible prejudices that come with using of the English language. The predominance of English may suggest that studies conducted in countries where the language is not spoken have been overlooked, which could result in a bias and a gap in scientific understanding.